2021
DOI: 10.1136/annrheumdis-2021-eular.164
|View full text |Cite
|
Sign up to set email alerts
|

Ab0834 development of a Conceptual Framework for a Patient Reported Outcome Measure to Capture Patients’ Perceptions of Glucocorticoid Therapy During Treatment for Rheumatic Diseases

Abstract: Background:Glucocorticoids (GCs) are a key treatment for the autoimmune rheumatic diseases; however, they produce numerous physical and psychological side effects.1 The Outcome Measures in Rheumatology (OMERACT) Glucocorticoid Working Group have identified that there are no Patient Reported Outcome Measures (PROMs) for assessing the impact of systemic GC therapy across multiple rheumatic diseases from the patient’s perspective.2,3Objectives:The aim is to explore the impact of GCs on the symptoms and health-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The OMERACT Glucocorticoid Working Group has identified this as a key area for future work 137 and Bridgewater et al have recently presented a conceptual framework that will be used in the development of a steroid-specific PROM. 138 This will be of particular interest for AAV patients given the frequent need for long-term steroids.…”
Section: Outcome Measures In Aavmentioning
confidence: 99%
“…The OMERACT Glucocorticoid Working Group has identified this as a key area for future work 137 and Bridgewater et al have recently presented a conceptual framework that will be used in the development of a steroid-specific PROM. 138 This will be of particular interest for AAV patients given the frequent need for long-term steroids.…”
Section: Outcome Measures In Aavmentioning
confidence: 99%
“…The OMERACT Vasculitis Working Group had identified large variability in outcome measures in Behc ¸et's syndrome which included PROM data [43]. In 2004 a disease-specific PRO was developed in the UK, the Behc ¸et's Disease Quality of Life Scale (BD-QoL) [44] using 30 questions that have also been adapted for use in Korean and Arabic speaking patients [45].…”
Section: Behc ¸Et's Diseasementioning
confidence: 99%
“…This has resulted in a checklist of items to report key glucocorticoid adverse effects (the GTI) which has now been incorporated into clinical trials within vasculitis [18]. The OMERACT group have identified that a PRO to capture impact from the patient perspective is needed and work to develop a Steroid PRO based on underpinning qualitative interviews with patients from the UK, USA and Australia is currently underway [45].…”
Section: Impact Of Glucocorticoids In Systemic Vasculitidesmentioning
confidence: 99%